Perceptions, experiences and views of nurses, patients and families on bedside handover practices: A scoping review. - Neo Mofokeng Mokganya; Siyanda; Bale; Tendani (Student's Journal of Health Research Africa, 2026)
Background Bedside handover is increasingly recognised as a means of promoting patient-centred care, improving patient safety, and enhancing communication. Its implementation varies across healthcare settings, and the perception of nurses towards it plays a critical role. The purpose of this scoping reviewwas to identify and map the existing literature on the perceptions, experiences, and views of nurses, patients, and families regarding bedside handover. Methods The review followed the PRISMA-ScR guidelines. A comprehensive search of studies published between 2020 and 2025 was conducted across electronic databases, including Scopus, PubMed, EBSCO-Host, and Google Scholar. The search was limited to articles written in English. A scoping review was conducted to examine nursing handover practices. Studies published between 2020 and 2025 that investigated nursing handover, bedside handover, communication, handover tools, and related outcomes were eligible for inclusion. Data were charted using a structured extraction form capturing author, year, country, design, population, sample size, tools, and key findings. Results A total of 13 studies met the final eligibility criteria. Across the included studies, nurses, patients, and families generally viewed bedside handover positively, particularly regarding its contribution to communication, patient involvement, continuity of care, and patient safety. However, concerns relating to confidentiality, workload, environmental barriers, and the lack of standardised handover processes influenced experiences and perceptions of bedside handover across healthcare settings. Conclusion Effective handovers, driven by standardised tools and clear communication, are vital for patient safety. Strengthening institutional support and patient involvement optimises clinical transitions, ultimately improving healthcare efficiency and long-term medical outcomes.